A colorimetric, sensitive, rapid, and simple diagnostic kit for the HLB putative causal agent detection - Stolowicz, Fabiana; Larocca, Luciana; Werbajh, Santiago; Parma, Yanil; Carrillo, Carolina; Ogas, Lorena; Agostini, Juan Pedro; Redes, Jonathan; Welin, Bjorn; Castagnaro, Atilio; Vojnov, Adrian (Frontiers in Agronomy, 2022)
Huanglongbing (HLB) is one of the most devastating diseases in citrus worldwide. The Gram-negative bacterial plant pathogen, “Candidatus Liberibacter spp”., is phloem-limited and vectored by citrus psyllids. The species “Candidatus Liberibacter asiaticus” (C.Las) has been detected in Argentina, and its vector has been found at least in nine provinces. Early detection of C.Las is critical for a successful management of HLB disease. Currently, HLB molecular diagnosis is carried out by PCR, Nested PCR, real time PCR or another combination of these techniques, which require purification of genomic DNA, sophisticated equipment and highly trained personnel. We have developed a prototype of a sensitive colorimetric kit to detect C.Las, based on specific DNA isothermal amplification of this microorganism. The reaction buffer contains hidroxynaphthol blue (HNB), an indicator dye that turns from violet to blue/light blue when the DNA amplification reaction is positive. Similar sensitivity to visualize a positive reaction was observed between HNB-LAMP and agarose gel electrophoresis analysis. The detection of C.Las infected plants was up to 8 ng, of total infected plant genomic DNA, similar to Real Timeq PCR. A blind validation test of the prototype kit was performed with purified DNA extracted from healthy or C.Las infected midribs plants. Our kit showed 100% concordance with the results of gold standard qPCR technique, applied by the Laboratorio de Biología Molecular de EEA Montecarlo. The analysis of samples, without DNA purification to detect C.Las, showed a similar sensitivity to the analysis of the same samples in which C.Las DNA was previously purified.